Ultra-early endovascular treatment improves prognosis in High grade aneurysmal subarachnoid hemorrhage: A single-center retrospective study - Wu, Botao; Huang, Zhe; Liu, Huan; He, Jiayao; Ju, Yan; Chen, Ziwei; Zhang, Taiwei; Yi, Fuxin (Frontiers in Neurology, 2022)
Background The long-term survival prognosis of patients with high-grade (Hunt-Hess grade IV–V or World Federation of Neurosurgical Societies grade IV–V) aneurysmal subarachnoid hemorrhage (aSAH) is generally poor, and the association between endovascular treatment timing and the prognosis of high-grade aSAH has not been explored in depth. This retrospective cohort study aimed to determine whether endovascular treatment within 24 h of high-grade aSAH is associated with a better prognosis. Methods We retrospectively analyzed the clinical data of patients with high-grade aSAH who were admitted to our institution between January 2018 and January 2021. The Modified Rankin Scale score was used to assess the 6-month prognosis of patients. Univariate and multivariate logistic regression analyses were used to identify the factors associated with prognosis. The area under the receiver operating characteristic (ROC) curve was used to assess the model's discriminatory ability. Results Eighty-six patients were included in the study. In the multivariate analysis, the timing of endovascular treatment (odds ratio = 7.003 [1.800–27.242], P = 0.005) was an independent risk factor for prognosis. The ROC curve showed that the predictive power of the timing of endovascular treatment was 0.744, the best cut-off value was 12.5 h, and the corresponding sensitivity and specificity were 71.4 and 70.5%, respectively. Hydrocephalus (P = 0.005) and pulmonary infection (P = 0.029) were also associated with prognosis. In addition, cerebrospinal fluid drainage immediately after endovascular treatment had a significant effect on reducing hydrocephalus formation. Conclusions Endovascular therapy within 24 h is feasible and improves the prognosis of patients with high-grade aSAH.